Indistinguishable Gender Ideology and the Transcendence of Bissu Gender in Bugis–Makassar Literary Representations - Nur Aina Ahmad; Hasanuddin Fatsah; Sitti Rachmi Masie; Salam Salam (RIRAI Publisher, 2026)
Indistinguishable gender ideology in literary works refers to a concept in which the roles, attributes, and social positions of female and male characters are no longer confined by traditional binary stereotypes (masculine–feminine) or biological determinism. This concept is closely related to gender transcendence, understood as an ideological meaning rooted in the internal cultural framework of Bugis–Makassar society. This study examines the representation of indistinguishable gender ideology and the transcendence of Bissu gender in modern Indonesian literature set within the socio-cultural context of Bugis–Makassar society in South Sulawesi. It analyzes how gender roles, characteristics, and issues are constructed and represented in selected literary works. Focus of research includes the shifts in gender narratives over time, the stereotypes that are reproduced or deconstructed, and the social implications of these representations. The study employs a qualitative descriptive content analysis method applied to a selection of significant novels, short stories, and poems within the canon of modern Indonesian literature. Data were collected through close reading of literary texts, identification of patterns in the portrayal of male and female characters, and thematic analysis of issues related to identity, power, and gender relations.The findings reveal that Bissu transcend conventional gender categories, integrating both masculine and feminine elements within a single embodied existence, and are regarded as cosmologically “complete” beings. In this context, Bissu do not occupy a position of gender absence; rather, they exist at a different ontological level beyond ordinary gender divisions, functioning as intermediaries between the human and the spiritual realms.